Effectiveness of Connections Type on Vibration Response of Steel Beam - Ehab Ghazi Al-Hasany; Ashraf Hameed Alsalmani; Salah S. Al-Zaidee (Salehan Institute of Higher Education, 2019)
In a steel structure, choosing the connections type are one of the most important parameters in design consideration. How a connection type affects the vibration of steel beams has been investigated in this paper. The most effective connection type in reducing beam vibration has been highlighted. The study was conducted using different finite element models to simulate each connection type. Firstly, the model was validated by comparing its results with the results obtained by the analytical approach. In the numerical model, a linear frequency analysis was performed to determine beam natural frequency, then it has been compared with the corresponding value obtained by the Euler-Bernoulli approximations for simply supported beams. After that, two analysis procedures have been executed, steady-state analysis and transient analysis. In the steady-state analysis, a harmonic load with different frequencies was applied to the beam mid-span, while an impulsive load has been applied in the transient analysis. The results indicate that the deflection could be reduced by 72%, furthermore steady vibration of the beam can be reduced by 81% with using one of the moment connections instead of the traditional shear connection.